EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD MELALUI TEKNIK HANDS ON MATHEMATICS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK SISWA KELAS VIII MTsN BALAI SELASA - Okviani Syafti; Sefrinal Sefrinal (STKIP Pesisir Selatan, 2017)
This research began from issues of the low Mathematicabilities students of class VIIIMTsN Balai Selasa.This research is aimed to reveal the effect of Cooperatif modelswith Hands On Mathematic in mathematicstudents ability started from highand low, as well as the interaction between the model and the learning ability of students in influencing early understanding concept ability. This research is a quasi experimental design. The population in this research is all students of class VIIIMTsN Balai Selasa. The sampling technique used is Random Sampling. Samples of this research are the students of class VIII.2 as the experimental class and class VIII.4 as the control class. The instrument used is a test consists of beginning capabilities test and Posttest to see the understanding-concept ability. Data analysis was performed using t-test and ANAVA two ways for interaction.There are some conclusions that can be acquired based on the results of research and discussion. First, the students which use cooperative learning STAD type with hands on mathematics technic have higher understanding-concept abilitythan students that use the conventional learning. Second, the high starting students abilityunderstanding-concept ability higher than students low starting students ability. Third, there is no interaction between the model of learning and the prior knowledge of students in influencing the understanding conceptmathematical ability.Keywords : Model Pembelajaran Kooperatif Tipe STAD, Hands On Mathematics, Pemahaman Konsep, Kemampuan Awal.